Conflict related trauma in an Asian country: A report from Sri Lanka - De Zoysa, P. (My University, 2001)
This paper discusses the psychological aspects of the armed conflict that has ravaged Sri Lanka for many years. It briefly reviews the psychological correlates and consequences of war, with a special emphasis on the Sri Lankan context. Types of war trauma seen in Sri Lanka are discussed and research that has been conducted in the country is presented, where appropriate. Finally, the various organisations that have been set up for dealing with the psychological ramifications of war trauma are described.